Tariffs and welfare in new trade theory models - Gabriel Felbermayr; Benjamin Jung; Mario Larch (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
Arkolakis, Costinot and Rodriguez-Clare (ACR, 2012) prove that, conditional on the change in openness, the welfare gains from foreign trade reforms are quantitatively identical across single-sector trade models with radically different micro-foundations. We generalize this result to domestic and multilateral trade reforms. And we extend it to cover revenue generating import tariffs. This gives rise to a new type of welfare isomorphisms across models and liberalization scenarios and allows deriving a structurally identical optimal tariff formula. In contrast to the case of iceberg trade costs, welfare formulas based on tariff reforms are highly nonlinear and build on different types of trade elasticities and openness indices. Most importantly, the ACR iceberg formula necessarily underestimates the gains from trade. A stylized calibration of the model shows that the underestimation can be large.
urn:nbn:de:bsz:21-opus-63010
Keywords: F12; R12; 330; Gravity Equation; Monopolistic Competition; Heterogeneous Firms; Armington Model; International Trade; Trade Policy; Gains from Trade